Studi Logo Event (Acara) Di Daerah (Kajian Ikonografi: Studi Kasus Logo Karya Z. Hanafi di Sumatera Barat) - Budiman, Arif (Jurnal Bahasa Rupa, 2017)
Logoâs event become an art medium to express an image of event. From elements of line, shape, colour,  and typography which are composed unified, makes logo as a symbolic language. Logo can emphasize an identity of particular region from the diversity of local wisdom. West Sumatra which is in Minangkabau culture territority has its own concept on how human creativity reveal the messages. By a unique logo, it fulfills the aesthetic needs of society that interact people to participate the event. Theory of Iconography and Iconology reveal the meaning of logo from aesthetic aspect and aim behind the design. Zainul Hanafi is one of artist from West Sumatra that concern in graphic design.  Hanafi means logoâs event in specific region must have a concept that representate the importance of each stakeholder. The representation emerge the uses of diverse colours and shapes. Overlaps, crowded icons and rousing. Although there are many logo with more simple shapes, actually it is a valid diversity.